Red cell transfusion practices after stage 1 palliation: a survey of practitioners from the Pediatric Cardiac Intensive Care Society. (14th December 2019) - Badheka, Aditya; Yu, Priscilla; Mille, Felina; Durbin, Dennis; Elci, Okan; Blinder, Joshua
Abstract: Introduction: Neonates may require increased red cell mass to optimise oxygen content after stage 1 palliation; however, data informing transfusion practices are limited. We hypothesise there is a patient-, provider-, and institution-based heterogeneity in red cell transfusion decision-making after stage 1 palliation. Methods: We conducted an online survey of Pediatric Cardiac Intensive Care Society practitioners in 2016. Respondents answered scenario-based questions that defined transfusion indications and identified haematocrit transfusion thresholds. Respondents were divided into restrictive and liberal groups based on a haematocrit score. Fisher's exact test was used to determine the associations between transfusion likelihood and patient, provider, and institutional characteristics. Bonferroni correction was applied to adjust the p-value to 0.004 for multiple comparisons. Results: There was a 21% response rate (116 responses). Most were male (58.6%), attending physicians (85.3%) with >5 year of intensive care experience (88.7%) and subspeciality training in critical care medicine (47.4%). The majority of institutions were academic (96.6%), with a separate cardiac ICU (86.2%), and performed >10 stage 1 palliation cases annually (68.1%). After Bonferroni correction, there were no significant patient, respondent, or institutional differences between the restrictive and liberal groups. No respondent or institutional characteristics influenced transfusion decision-making after stage 1 palliation. Conclusions: Decision-making around red cell transfusion after stage 1 palliation is heterogeneous. We found no clear relationships between patient, respondent, or institutional characteristics and transfusion decision-making among surveyed respondents. Given the lack of existing data informing red cell transfusion after stage 1 palliation, further studies are necessary to inform evidence-based guidelines.